Establishing frequency speed of kick test classificatory tables in male and female taekwondo athletes - Ferreira da Silva Santos, J.; Herrera-Valenzuela, T.; Franchini , E. (Kinesiology, 2019)
Recently, the Frequency Speed of Kick Test (FSKT10s) and its intermittent version (5 x 10s/10s intervals, FSKTmult) have been used to assess physical fitness of taekwondo athletes, but no classificatory normative table was found for these tests. Thus, the aim of the study was to present two normative classificatory tables for both the FSKT10s and FSKTmult for male and female taekwondo athletes. One hundred fifteen male taekwondo athletes (median [interquartile range] age: 20 [17;27] years; body height: 175 [170;182] cm; body mass: 67 [60;78] kg; experience time: 6 [3;10] years) and seventy female taekwondo athletes (median [interquartile range] age: 19 [(17;24] years; body height: 162 [157;169] cm; body mass: 57 [50;64] kg; experience time: 5 [3;9] years) volunteered to participate in the study. Their skills ranged between 4th gub and 2nd dan. All the participants were evaluated during their competitive period and were familiarized with this test. The classificatory tables are presented in five scales, as follows: excellent (=95th percentile); good (>75th percentile up to 94th percentile); regular (>25th percentile up to 74th percentile); poor (>6th percentile up to 24th percentile); and very poor (=5th percentile). The classificatory tables for FSKT10s and FSKTmult can help coaches and strength and conditioning professionals to classify performance and monitor the physical fitness of taekwondo athletes in different stages of training and during the competitive season.